Concepts in Periodic Discharges: A Descriptive Study - Khanna, Laxmi; Agarwal, Nandini; Kandel, Sabita (International Journal of Epilepsy, 2018)
Introduction Periodic discharges are now known as the ictal–interictal continuum and represent ongoing injury in acute or chronic neurological illnesses.Objective The aim of our study was to identify periodic discharges in patients who have undergone continuous bedside electroencephalography (EEG) monitoring and to classify the EEG according to the current American Clinical Neurophysiology Society terminology.Materials and Methods The continuous bedside EEG records of intensive care patients admitted from August 2017 to July 2018 were analyzed. The clinical spectrum, the treatment, and outcome of each of these patients were monitored.Results Fifty cases of periodic discharges (11 children, 39 adults) were identified over 1 year from 2017 to 2018. The clinical presentation included 32% seizures, 16% status epilepticus, 20% coma, 16% fever with altered sensorium, 8% abnormal behavior, 4% strokes, and 4% traumatic brain injury. The diagnosis was 20% autoimmune encephalitis, 8% herpes encephalitis, 20% multiorgan failure, 4% traumatic brain injury, 16% status epilepticus, 16% posthypoxic encephalopathy, 4% strokes, 4% intracerebral bleeds, 4% meningitis, and 4% severe dementia. Lateralized periodic discharges were identified in 20%, bilateral independent periodic discharges in 20%, and generalized periodic discharges in 60%. Fifty-six percent patients recovered with residual neurological deficits and 44% succumbed to their illness.Conclusions Continuous bedside EEG monitoring has revolutionized the approach to seizures in critically ill patients. Despite a vigilant approach and diligent diagnosis of these abnormal rhythms, the mortality rate was 20% in patients with lateralized periodic discharges and 60% with bilateral and generalized periodic discharges (p ≤ 0.05).
Keywords: electroencephalogram; encephalitis; epilepsy; periodic discharges; stroke